2019
DOI: 10.1249/mss.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity and Exercise on Bone Marrow Progenitor Cells after Radiation

Abstract: Introduction The late effects of radiation therapy can have significant consequences for the health and quality of life of long-term cancer survivors. Radiation induces persistent alterations in hematopoietic stem and progenitor cells (HSPC) and the bone marrow environment; however, how relevant host factors such as obesity and exercise differentially regulate HSPC content and the bone marrow environment after radiation exposure remains unknown. The purpose of this investigation was to evaluate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Although it has been well accepted that exercise training is an effective method for treatment of IR induced by HFD-associated obesity, the clear mechanism by which exercise training attenuates adipose tissue inflammation to attenuate IR remains to be elucidated ( Macpherson et al, 2015 ; Emmons et al, 2019 ; Luo et al, 2020 ). Given the decreases of inflammation in downhill running and dietary regulation-treated mice, we further interested if exercise training and dietary regulation present similar effects on macrophages ( Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been well accepted that exercise training is an effective method for treatment of IR induced by HFD-associated obesity, the clear mechanism by which exercise training attenuates adipose tissue inflammation to attenuate IR remains to be elucidated ( Macpherson et al, 2015 ; Emmons et al, 2019 ; Luo et al, 2020 ). Given the decreases of inflammation in downhill running and dietary regulation-treated mice, we further interested if exercise training and dietary regulation present similar effects on macrophages ( Luo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Observations in exercise trials on the incidence/duration of neutropenia and related criteria Emmons et al, 2019;Marędziak, Śmieszek, Chrząstek, Basinska, & Marycz, 2015). Furthermore, the proliferative capacity of stem and progenitor cells in the bone marrow was increased in voluntary lifelong exercising rats compared to sedentary controls (Stelzer et al, 2010).…”
Section: Long-term Effects On Haematopoietic Progenitor Cellsmentioning
confidence: 97%
“…Additionally, studies presenting inflammatory markers when exposed to radiation found that IL-1, IL-6, TNF-α, and TGF-β levels decreased in the intervention group that exercised. Emmons et al ( 27 ) also reported that progressive treadmill exercise in mice before exposure to γ-rays decreased bone marrow ROS levels (effect size 0.75). Studies reporting DNA damage with respect to micro-nucleation, Caspase 3/7 activity, and γH2AX foci indicating DNA DSBs all favored the intervention group with effect sizes ranging from 0.65 to 1.10 ( Figure 3 ) ( 27 , 37 42 ).…”
Section: Resultsmentioning
confidence: 95%
“…Cellular and tissue function outcomes were assessed with whole-body irradiations only, but showed effect sizes in favor of aerobic exercise with regard to bone marrow cellularity, reticulocytosis, metabolic enzyme activity, and bone mineralization/density ( 27 , 37 , 38 , 54 ). Emmons et al ( 27 ) reported that exercised mice had increased bone marrow cellularity, decreased marrow adipose tissue, and increased Lin − Sca-1 + c-kit + (LSK) cell populations as a response to exercise suggesting rescue of hematopoietic stem cells that were destructed by γ-irradiation, with effect sizes ranging from 0.81 to 1.49. Increased reticulocytosis and metabolic enzyme activity was observed when mice progressively exercised for 10 weeks after exposure to γ-rays compared to control ( 37 , 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation